ANALYSIS OF FACTORS CONTRIBUTING TO SHORTAGES AND STOCKOUTS OF ESSENTIAL MEDICINES IN KINDU HEALTH ZONE FACILITIES FROM JANUARY 1, 2021 TO DECEMBER 31, 2022 - Janvier BAMBALATI SABITI,; OKUNDI DIUMU Stanis,; NGWABI WA LUZINDIA Asaph,; ABELI ZUNGULIKA Joseph, (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2025)
This research, titled “Analysis of Contributing Factors to Shortages and Stock-Outs of Essential Medicines in Health Facilities in the Kindu Health Zone from January 1, 2021, to December 31, 2022,” aimed to understand the causes, consequences, and possible solutions to these recurring shortages. Conducted in 13 health facilities, the study found that all of them (100%) experienced frequent stock-outs, mainly occurring monthly (61.5%). The main causes identified were the inefficiency of the supply system, failure to meet delivery deadlines, lack of staff training, inadequate management tools, and diversion of medicines. The major consequences included a decline in health facility attendance (76.9%), reduced effectiveness of healthcare (15.4%), and a negative impact on public health. The authors recommend strengthening planning and needs quantification, improving stock management and financing, training staff, and ensuring better coordination among health system actors. Shortages of essential medicines remain a major public health challenge in the Kindu/Maniema region and across the DRC, requiring coordinated action to ensure continuous and equitable access to vital drugs.